2019
DOI: 10.33963/kp.14846
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the risks of incident atrial fibrillation: a narrative review. Part 2

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia with increasing incidence worldwide. Much focus has been directed towards AF prevention, given the morbidity and mortality from stroke, heart failure, and dementia. There are a number of common conditions associated with the onset of AF including, but not limited to, increased alcohol consumption, body weight, exercise, and stress. To reduce the incidence of AF, public health campaigns and targeted patient interventions may be warranted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Additionally, they were asked about specific characteristics known to be associated with AF (age, sex, diabetes, hypertension). Some traditional risk factors were not assessed in the survey and thus were not able to be measured in this study (obesity, alcohol use, smoking) [14,15]. Questions regarding training characteristics were open-ended and did not specify a specific time range (e.g., years of running was queried as “For how many years have you been running?”).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they were asked about specific characteristics known to be associated with AF (age, sex, diabetes, hypertension). Some traditional risk factors were not assessed in the survey and thus were not able to be measured in this study (obesity, alcohol use, smoking) [14,15]. Questions regarding training characteristics were open-ended and did not specify a specific time range (e.g., years of running was queried as “For how many years have you been running?”).…”
Section: Methodsmentioning
confidence: 99%
“…19,45,[54][55][56][57][58] Symptomatic recurrence of paroxysmal AF was documented more commonly in regular drinkers than in those who did not consume alcohol (50% vs 24%) and daily alcohol intake was an independent predictor of AF relapse. 54 In addition, moderate -to -high alcohol consumption is an independent risk factor for progression of paroxysmal toward chronic AF (OR, 3). 55 Several studies demonstrated improvement in AF ablation outcome with alcohol abstinence after the procedure, [56][57][58] reporting that abstainers compared with former or current drinkers had a significantly lower AF recurrence rate after the first ablation (34.1% vs 41.9%).…”
Section: 51mentioning
confidence: 99%
“…Glucose tolerance test Low-glycemic index diet Metformin Pioglitazone HYPERTENSION BP, 125-130/80-85 mm Hg ACEI, ARB, and/or eplerenone β-blockers Renal denervation FIGURE 1 A practical guide for risk factors modification to prevent atrial fibrillation. Abbreviations: BP, blood pressure; CRF, cardiorespiratory fitness; LDL -C, low -density lipoprotein cholesterol; MET, metabolic equivalent (of task); TG, triglycerides; others, see TABLES [2][3][4]…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is known to be an independent predictor of mortality [1][2][3]. Moreover, patients receiving anticoagulation most often die from cardiovascular causes [4].…”
Section: Introductionmentioning
confidence: 99%